2023
DOI: 10.1117/1.nph.10.2.023515
|View full text |Cite
|
Sign up to set email alerts
|

Using preregistration as a tool for transparent fNIRS study design

Abstract: Significance: The expansion of functional near-infrared spectroscopy (fNIRS) methodology and analysis tools gives rise to various design and analytical decisions that researchers have to make. Several recent efforts have developed guidelines for preprocessing, analyzing, and reporting practices. For the planning stage of fNIRS studies, similar guidance is desirable. Study preregistration helps researchers to transparently document study protocols before conducting the study, including materials, methods, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 176 publications
1
27
0
Order By: Relevance
“…Acknowledging the intricacies presented by this pilot study, we advocate for the adoption of preregistration in subsequent research endeavors. This approach, as championed by Schroeder et al (2023) , will enhance the clarity and reproducibility of our scientific inquiry, allowing the researcher to systematically address biases and substantiate the reliability of our results.…”
Section: Discussionmentioning
confidence: 99%
“…Acknowledging the intricacies presented by this pilot study, we advocate for the adoption of preregistration in subsequent research endeavors. This approach, as championed by Schroeder et al (2023) , will enhance the clarity and reproducibility of our scientific inquiry, allowing the researcher to systematically address biases and substantiate the reliability of our results.…”
Section: Discussionmentioning
confidence: 99%
“…We encourage future efforts to use the CRED-nf checklist 26 to ensure best practice guidelines are followed and rigorous experimental designs continue to be adopted. We also encourage researchers to continue to pre-register their trials and we hope that the documentation of this experiment will inform more detailed pre-registered study protocols in the future 41,42,43 . Lastly, while the present study focused on motor rehabilitation in PD, the shown proof-of-concept for a multi-session supervised neurofeedback experiment in a home-setting may encourage exploration of other clinical use cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, we took care to keep the contribution of systemic physiological changes in our design to a minimum and assessed the robustness of the online analysis through an additional offline analysis using more stringent preprocessing methods. More state-of-the art online artifact control measures and signal processing methods (Klein and Kranczioch, 2019; Lühmann et al, 2020; Klein et al, 2022; Schroeder et al, 2023) are now available and can be used in future studies to sufficiently rule out the contributions of systemic physiology.…”
Section: Discussionmentioning
confidence: 99%